Honey sugars profile of stingless bee Tetragonula laeviceps (Hymenoptera: Meliponinae) - Ali Agus; Agussalim Agussalim; Muhamad Sahlan; Ardo Sabir (Society for Indonesian Biodiversity, 2021)
Abstract. Agus A, Agussalim, Sahlan M, Sabir A. 2021. Honey sugars profile of stingless bee Tetragonula laeviceps (Hymenoptera: Meliponinae). Biodiversitas 22: 5205-5210. Honey was a functional food to improve human health, but irresponsible people used this circumstance to make fake honey. This study aimed to evaluate the profile of the sugar of stingless bee honey [Tetragonula laeviceps (Smith, 1857)] from different geographical origins in Indonesia. Honey, three samples were directly collected from three other sources for meliponiculture of T. laeviceps in Indonesia: Sleman, Klaten, and Gunungkidul. The honey sugars profile was analyzed: glucose, fructose, sucrose, reducing sugar, the sum of fructose and glucose, glucose to moisture ratio, fructose to glucose ratio, and honey pH. Glucose and fructose were analyzed by HPLC, sucrose by Luff Schoorl, reducing the sugar by Layne-Enyon, and pH by a pH meter. The current findings revealed that the geographical origins had a highly significant effect on glucose, fructose, the sum of fructose and glucose, glucose to moisture ratio, fructose to glucose ratio, and honey pH (P<0.01) and significant effect on reducing sugar (P<0.05), but not on sucrose content. Thus, it can be concluded that the origins were affecting the honey sugars profile and honey from Sleman has the highest sugars content, followed by honey from Klaten and the lower was honey from Gunungkidul.